2015 IEEE 13th International Conference on Industrial Informatics (INDIN) 2015
DOI: 10.1109/indin.2015.7281960
|View full text |Cite
|
Sign up to set email alerts
|

From textual programming to IEC 61499 artifacts: Towards a model-driven engineering approach for smart grid applications

Abstract: During the last years the increasing installation of distributed energy resources, electric vehicles bus also energy storage systems has lead to new challenges in terms of power system planning and operation. New intelligent approaches turning power distribution grids into Smart Grids are necessary. For their realization standardized automation, control and communication systems are essential. Moreover, an integrated engineering approach for the development of Smart Grid applications using these standards is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Therefore, based on the reviewed studies we may conclude that the MDE approach for power systems applications development is a subject having considerable research activity. Particularly in the area of automation and smart grids applications, several studies have been identified, however a considerable number of publications apparently originate in the same research group, since they have some authors in common (references [4], [33]- [36], [38], [40]- [42], [45], [47]). On the other hand, since only a few studies related to the area of EMS have mentioned MDE concepts, we can infer that those techniques are not widespread in the development of EMS applications.…”
Section: B Answers To Research Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, based on the reviewed studies we may conclude that the MDE approach for power systems applications development is a subject having considerable research activity. Particularly in the area of automation and smart grids applications, several studies have been identified, however a considerable number of publications apparently originate in the same research group, since they have some authors in common (references [4], [33]- [36], [38], [40]- [42], [45], [47]). On the other hand, since only a few studies related to the area of EMS have mentioned MDE concepts, we can infer that those techniques are not widespread in the development of EMS applications.…”
Section: B Answers To Research Questionmentioning
confidence: 99%
“…• The Eclipse Atlas Transformation Language (ATL) is used by [38] to describe rules for transforming textual programming languages into IEC 61499 applications. The ATL is also used by [40] for defining transformation rules mapping control applications, modeled using Matlab/Simulink, into IEC 61499 applications.…”
Section: ) Transformation Engines and Generatorsmentioning
confidence: 99%